Pinpointing P450s associated with pyrethroid metabolism in the dengue vector, Aedes aegypti: developing new tools to combat insecticide resistance. - Bradley J Stevenson; Patricia Pignatelli; Dimitra Nikou; Mark J I Paine (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: Pyrethroids are increasingly used to block the transmission of diseases spread by Aedes aegypti such as dengue and yellow fever. However, insecticide resistance poses a serious threat, thus there is an urgent need to identify the genes and proteins associated with pyrethroid resistance in order to produce effective counter measures. In Ae. aegypti, overexpression of P450s such as the CYP9J32 gene have been linked with pyrethroid resistance. Our aim was to confirm the role of CYP9J32 and other P450s in insecticide metabolism in order to identify potential diagnostic resistance markers. METHODOLOGY/PRINCIPAL FINDINGS: We have expressed CYP9J32 in Escherichia coli and show that the enzyme can metabolize the pyrethroids permethrin and deltamethrin. In addition, three other Ae. aegypti P450s (CYP9J24, CYP9J26, CYP9J28) were found capable of pyrethroid metabolism, albeit with lower activity. Both Ae. aegypti and Anopheles gambiae P450s (CYP's 6M2, 6Z2, 6P3) were screened against fluorogenic and luminescent substrates to identify potential diagnostic probes for P450 activity. Luciferin-PPXE was preferentially metabolised by the three major pyrethroid metabolisers (CYP9J32, CYP6M2 and CYP6P3), identifying a potential diagnostic substrate for these P450s. CONCLUSIONS/SIGNIFICANCE: P450s have been identified with the potential to confer pyrethroid resistance in Ae.aegypti. It is recommended that over expression of these enzymes should be monitored as indicators of resistance where pyrethroids are used.